2022
DOI: 10.3390/met12111782
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Selective Laser Melting Processes for Minimizing Energy Consumption and Maximizing Product Tensile Strength

Abstract: As a sustainable manufacturing technology, selective laser melting (SLM) is a typical additive manufacturing (AM) method with high flexibility and material efficiency. However, SLM is intrinsically energy-intensive than conventional machining processes. By contrast, part quality, especially the tensile strength, is critical for applying SLM technology. Therefore, this study aims to minimize the process energy consumption and maximize the part tensile strength by optimizing three essential process parameters, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…During that period, researchers concentrated their efforts on enhancing the thermal and exergy efficiency while minimizing energy losses in individual pieces of equipment, guided by the principles of the first and second laws of thermodynamics. It has been emphasized that effective measures to reduce energy loss and enhance efficiency involve adjustments to material structure, technological parameters, structural parameters, and so on [10][11][12]. For instance, Feng et al [13] optimized the sintering cooling machine, aiming to maximize exergy output.…”
Section: Introductionmentioning
confidence: 99%
“…During that period, researchers concentrated their efforts on enhancing the thermal and exergy efficiency while minimizing energy losses in individual pieces of equipment, guided by the principles of the first and second laws of thermodynamics. It has been emphasized that effective measures to reduce energy loss and enhance efficiency involve adjustments to material structure, technological parameters, structural parameters, and so on [10][11][12]. For instance, Feng et al [13] optimized the sintering cooling machine, aiming to maximize exergy output.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that rubber recoating blades with a larger contact surface area and mid-range recoating velocities (10-80 mm/s) yield more uniform and compact powder layers, improving the printing quality while reducing the risk of recoater damages. Finally, it was found that the recoating speed directly affects the inter-layer cooling time and, thus, the heat accumulated in the build as well as its mechanical response [30,31]. Hence, using the right recoating speed helps to reduce the risk of the recoater impacting the deformed geometry of the AM build.…”
Section: Introductionmentioning
confidence: 99%
“…This approach yielded favourable trade-offs for dimensional accuracy and surface roughness. Similarly, Zhu et al [21] employed the NGSA-II algorithm to optimize tensile strength and energy consumption in the Selective Laser Melting (SLM) process. Chinchanikar et al [22] harnessed NSGA-II to minimize surface roughness and enhance tensile strength.…”
Section: Introductionmentioning
confidence: 99%